2012
DOI: 10.1590/s0103-64402012000400022
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine does not increase immediate bond strength of etch-and-rinse adhesive to caries-affected dentin of primary and permanent teeth

Abstract: The aim of this study was to evaluate the effect of 2% chlorhexidine digluconate (CHX) on immediate bond strength of etch-andrinse adhesive to sound (SD) and caries-affected (CAD) primary dentin compared with permanent dentin. Flat dentin surfaces from 20 primary molars (Pri) and 20 permanent molars (Perm) were assigned to 8 experimental groups (n=5) according to tooth type (Pri or Perm), dentin condition (SD or CAD -pH-cycling for 14 days) and treatment (control -C or 60 s application of 2% CHX solution after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 17 publications
6
37
0
4
Order By: Relevance
“…[31,41] Moreover, the use of CHX on CAD might have inhibited the degradation of adhesivedentin bonds more greatly than in sound dentin. [35] In addition, the application of CHX on CAD surfaces in the present study might have allowed for deeper penetration of CHX into the intertubular dentin, which is vulnerable to the action of MMPs, [35] resulting in an increased bond strength.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[31,41] Moreover, the use of CHX on CAD might have inhibited the degradation of adhesivedentin bonds more greatly than in sound dentin. [35] In addition, the application of CHX on CAD surfaces in the present study might have allowed for deeper penetration of CHX into the intertubular dentin, which is vulnerable to the action of MMPs, [35] resulting in an increased bond strength.…”
Section: Discussionmentioning
confidence: 91%
“…[4] In addition, dentin adhesives cannot penetrate as deeply into demineralized intertubular structures as acids can, which results in a lower μTBS than that of sound dentin. [1,35] Arrais et al [1] reported that acid-etching, even for an extended period of time, did not increase the bond strength of CAD over that of sound dentin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, applying the primer and bonding agent in separate steps increases the hydrophobicity of the adhesive layer, thus reducing water flow in the dentin tubules [42]. In a study by Lenzi et al [43], chlorhexidine also failed to influence immediate bonding strength to caries-affected dentin in permanent teeth, using a conventional two-step adhesive system. On the other hand, Shafiei et al [38] tested the influence of pretreatment with 2% chlorhexidine on the bond strength of two self-etch, two-bottle adhesive systems to healthy dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Lenzi et al 13 pesquisaram a influência da clorexidina no aumento da resistência adesiva na utilização de sistemas de três passos, em dentes permanentes com dentina afetada. Verificaram e confirmaram que a utilização da clorexidina não interfere na resistência adesiva quando aplicada em dentes com dentina afetada.…”
Section: Revisão Da Literaturaunclassified